Challenges in Mathematical Cognition: A Collaboratively-Derived Research Agenda - Alcock Lara; Ansari Daniel; Batchelor Sophie; Bisson Marie-Josée; De Smedt Bert; Gilmore Camilla; Göbel Silke M.; Hannula-Sormunen Minna; Hodgen Jeremy; Inglis Matthew; Jones Ian; Mazzocco Michèle; et al. (PsychOpen, 2022)
This paper reports on a collaborative exercise designed to generate a coherent agenda for research on mathematical cognition. Following an established method, the exercise brought together 16 mathematical cognition researchers from across the fields of mathematics education,psychology and neuroscience. These participants engaged in a process in which they generated an initial list of research questions with the potential to significantly advance understanding of mathematical cognition, winnowed this list to a smaller set of priority questions, and refined the eventual questions to meet criteria related to clarity, specificity and practicability. The resulting list comprises 26 questions divided into sixbroad topic areas: elucidating the nature of mathematical thinking, mapping predictors and processes of competence development, charting developmental trajectories and their interactions, fostering conceptual understanding and procedural skill, designing effective interventions, and developing valid and reliable measures. In presenting these questions in this paper, we intend to support greater coherence in both investigation and reporting, to build a stronger base of information for consideration by policymakers, and to encourage researchers to take a consilient approach to addressing important challenges in mathematical cognition.